Media law essentials. - Maule, Douglas (Edinburgh law essentials., 2010)
Your guide to media law in the UK, full of cases and helpful student features. From official secrets to breach of confidence, and from reporting restrictions to racial hatred, Media Law Essentials is your concise guide to the laws that govern the news and media in the UK. Summary sections of Essential Facts and Essential Cases will help you to quickly learn and revise the key elements of the subject.